2019
DOI: 10.1177/1847979019866337
|View full text |Cite|
|
Sign up to set email alerts
|

Examination of explicit definitions of enterprise architecture

Abstract: Various understandings of enterprise architecture (EA) exist and there is no agreement on them. The various definitions of EA are not always complementary but sometimes in opposition. Within this study, we conduct a systematic literature review to analyze explicit definitions of EA. Based on concepts from the academic field of terminology, we have broken down these definitions into many parts in order to examine each part individually before making generalizations. The findings show how some of the EA definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…There are other views on EA's usefulness and reach, which stem from its various definitions (Saint-Louis, Morency & Lapalme, 2019). Nandico (2016) and Goerzig & Bauernhansl (2018) confirm Valenduc & Vendramin's (2016) observations, as they also show that it can contribute to creating sustainable competitive advantage, when used in the process of organizational modeling, by determining the logical components to use in applications, with their respective services, according to the established scope.…”
Section: Introductionmentioning
confidence: 79%
“…There are other views on EA's usefulness and reach, which stem from its various definitions (Saint-Louis, Morency & Lapalme, 2019). Nandico (2016) and Goerzig & Bauernhansl (2018) confirm Valenduc & Vendramin's (2016) observations, as they also show that it can contribute to creating sustainable competitive advantage, when used in the process of organizational modeling, by determining the logical components to use in applications, with their respective services, according to the established scope.…”
Section: Introductionmentioning
confidence: 79%
“…Researchers such as Saint-Louis et al ( 2019); Dang and Pekkola (2017); Foorthuis et al (2020); Banaeianjahromi and Smolander (2019); and Szabó and Öri (2017) led studies whose findings showed the importance of EA in supporting organizations in addressing complexity if EA is involved in the process of managing organization. These scholars established that organizations must develop models of EA frameworks in line with their business context to gain the maximum benefit of EA as a tool for addressing complexity.…”
Section: Enterprise Architecture and Healthcare Organizational Complexitymentioning
confidence: 99%
“…For example in smart cities context, the need to develop complex information systems has been amplified. Therefore, EA helps to address the problems of complexity of information systems deployed in cities [16]. Authors in [17] stated that the growing complexity and lack of integration across systems results in organizational barriers to stakeholder collaboration in smart cities.…”
Section: Enterprise Information Systems Engineering and Enterprise Ar...mentioning
confidence: 99%